Intranasal Galanin (1–15) modulates alcohol self-administration and depressive-like behavior in rats and shows a favorable safety profile - Cantero-García, Noelia; Flores-Burgess, Antonio; Flores-Gómez, Marta; Pineda-Gómez, Juan Pedro; Ramos, Maria C.; Diaz, Caridad; Millón, Carmelo; Díaz-Cabiale, Zaida (Frontiers in Pharmacology, 2025)
IntroductionGalanin is a neuropeptide in the central nervous system that regulates mood and alcohol consumption. Its N-terminal fragment, Galanin (1–15) [GAL (1–15)], has demonstrated specific behavioral effects, enhancing the efficacy of selective serotonin reuptake inhibitors (SSRIs) and reducing ethanol intake and alcohol self-administration in preclinical models. Additionally, GAL (1–15) combined with SSRIs decreases alcohol self-administration and depressive symptoms in a comorbid alcoholism-depression model. These findings suggest potential applications in the treatment of depression and alcohol use disorders. Given its therapeutic potential, evaluating the translational aspects and safety of GAL (1–15) is essential for clinical development.MethodsThis study investigated the intranasal administration of GAL (1–15), assessing its effects on depression-related behavior in the Forced Swim Test (FST) and alcohol self-administraation in an operant selfadministration model. To determine its safety profile, we evaluated GAL (1–15) for cardio toxicity (hERG channel inhibition), genotoxicity (micronucleus formation), and drug interactions (CYP450 inhibition).ResultsResults showed that intranasal GAL (1–15) exhibited a prodepressant effect, as previously demonstrated with its ICV administration. Furthermore, intranasal GAL (1–15) effectively reduced alcohol consumption. In vitro safety assessments revealed no adverse effects on cardiac function or genotoxicity at the concentrations studied, with minimal interaction with CYP450 enzymes, supporting its suitability for drug development.DiscussionIn conclusion, intranasal administration of GAL (1–15) represents a promising candidate for clinical trials due to its favorable safety profile and therapeutic potential. Its use appears particularly suitable as a standalone treatment for alcohol use disorder and, when combined with SSRIs, as a potential therapy for depressive disorders.